The AIP Model of EMDR Therapy and Pathogenic Memories - Hase, Michael; Balmaceda, Ute M.; Ostacoli, Luca; Liebermann, Peter; Hofmann, Arne (Frontiers in Psychology, 2017)
Eye Movement Desensitization and Reprocessing therapy has been widely recognized as an efficacious treatment for post-traumatic stress disorder (PTSD). In the last years more insight has been gained regarding the efficacy of EMDR therapy in a broad field of mental disorders beyond PTSD. The cornerstone of EMDR therapy is its unique model of pathogenesis and change: the adaptive information processing model (AIP). The AIP model developed by F. Shapiro has found support and differentiation in recent studies on the importance of memories in the pathogenesis of a range of mental disorders beside PTSD. However theoretical publica-tions or research on the application of the AIP model are still rare. The increasing acceptance of ideas that relate the origin of many mental disorders to the formation and consolidation of implicit dysfunctional memory, lead to formation of the theory of pathogenic memories. Within the theory of pathogenic memories these implicit dysfunctional memories are consid-ered to form basis of a variety of mental disorders. The theory of pathogenic memories seems compatible to the AIP model of EMDR therapy, which offers strategies to effectively acess and transmute these memories leading to amelioration or resolution of symptoms. Merging the AIP model with the theory of pathogenic memories may initiate research. In consequence patients suffering from such ‚memory based’ disorders may be earlier diagnosed and treated more effectively.